Enantioselective Deaminative Alkylation of Amino Acid Derivatives with Unactivated Olefins - Sun, Shang-Zheng; Cai, Yue-Ming; Zhang, De-Liang; Wang, Jia-Bao; Yao, Hong-Qing; Rui, Xi-Yan; Martin, Ruben; Shang, Ming (Journal of the American Chemical Society, 2022)
Herein, we report the first Ni-catalyzed enantioselective deaminative alkylation of amino acid and peptide derivatives with unactivated olefins. Key for success was the discovery of a new sterically encumbered bis(oxazoline) ligand backbone, thus offering a de novo technology for accessing enantioenriched sp 3 –sp 3 linkages via sp 3 C–N functionalization. Our protocol is distinguished by its broad scope and generality across a wide number of counterparts, even in the context of late-stage functionalization. In addition, an enantioselective deaminative remote hydroalkylation reaction of unactivated internal olefins is within reach, thus providing a useful entry point for forging enantioenriched sp 3 –sp 3 centers at remote sp 3 C–H sites.